Study on the mechanism of lactic acid bacteria and their fermentation broth in alleviating hyperuricemia based on metabolomics and gut microbiota - Rao, Lijuan; Dong, Biao; Chen, Yanru; Liao, Jiajing; Wang, Chen; Fu, Guiming; Wan, Yin (Frontiers in Nutrition, 2024)
Hyperuricemia (HUA) is a metabolic disease caused by purine metabolism disorders in the body. Lactic acid bacteria (LAB) and their fermentation broth have the potential to alleviate hyperuricemia, but the potential mechanism of action is still unclear. Therefore, in this study, LAB with high inhibitory activity against xanthine oxidase (XOD) were screened out. Then the fermentation broth, fermentation supernatant and fermentation bacteria after fermentation of these LAB were administered into HUA mice, respectively. Results showed that Lactobacillus reuteri NCUF203.1 and Lactobacillus brevis NCUF207.7, of which fermentation supernatant had high inhibitory activity against XOD, were screened out and administered into HUA mice. Among them, L. reuteri strain, L. reuteri fermentation broth, L. brevis fermentation broth and L. brevis fermentation supernatant could significantly reduce serum uric acid levels and inhibited the liver XOD activity in HUA mice. The GC-MS metabolomics analysis of colon contents showed that supplementation of these four substances could partially reverse the down-regulation of energy metabolism pathways such as ketone body metabolism, pyruvate metabolism and citric acid cycle in HUA mice. It could also regulate amino acid metabolism pathways such as alanine metabolism, arginine and proline metabolism, glycine and serine metabolism, and repair the disorders of amino acid metabolism caused by HUA. In addition, the intervention of L. brevis fermentation broth and L. brevis fermentation supernatant may also accelerate the catabolism of uric acid in the intestine by up-regulating the urea cycle pathway. Fecal 16S rRNA sequencing analysis showed that their intervention increased the diversity of gut microbiota in HUA mice and alleviated the gut microbiota dysregulation caused by HUA. These results indicated that the LAB and their fermentation broth may play a role in alleviating HUA by regulating intestinal metabolism and gut microbiota.